Diversity of Glycoprotein Deficiencies in Glanzmann’s Thrombasthenia - Meyer, M; Herrmann, F H (Thrombosis and Haemostasis, 1985)
The platelet proteins of 9 thrombasthenic patients from 7 families were analysed by high resolution two-dimensional gel electrophoresis (HR-2DE) and crossed immunoelectrophoresis (CIE). In 7 patients both glycoproteins (GPs) IIb and Ilia were absent or reduced to roughly the same extent. In two related patients only a trace of GP Ilb-IIIa complex was detected in CIE, but HR-2DE revealed a glycopeptide in the position of GP Ilia in an amount comparable to type II thrombasthenia. This GP Ilia-like component was neither recognized normally by anti-GP Ilb-IIIa antibodies nor labeled by surface iodination. In unreduced-reduced two-dimensional gel electrophoresis two components were observed in the region of GP Ilia. The assumption of a structural variant of GP Ilia in the two related patients is discussed.
Keywords: Thrombasthenia; Platelet membrane glycoproteins; Glycoprotein IIb-IIIa complex